From crust to core a chronicle of deep carbon science - Mitton, Simon 1946- (Cambridge University Press, 2020)
Carbon plays a fundamental role on Earth. It forms the chemical backbone for all essential organic molecules produced by living organisms. Carbon-based fuels supply most of society's energy, and atmospheric carbon dioxide has a huge impact on Earth's climate. This book provides a complete history of the emergence and development of the new interdisciplinary field of deep carbon science. It traces four centuries of history during which the inner workings of the dynamic Earth were discovered, and documents extraordinary scientific revolutions that changed our understanding of carbon on Earth forever: carbon's origin in exploding stars; the discovery of the internal heat source driving the Earth's carbon cycle; and the tectonic revolution. Written with an engaging narrative style and covering the scientific endeavours of more than a hundred pioneers of deep geoscience, this is a fascinating book for students and researchers working in Earth system science and deep carbon research